Aminolevulinate synthase: lysine 313 is not essential for binding the pyridoxal phosphate cofactor but is essential for catalysis. - Ferreira, G. C. (Cold Spring Harbor Laboratory Press, 1995)
5-Aminolevulinate synthase is the first enzyme of the heme biosynthetic pathway in animals and some bacteria. Lysine-313 of the mouse erythroid aminolevulinate synthase was recently identified to be linked covalently to the pyridoxal 5'-phosphate cofactor (Ferreira GC, Neame PJ, Dailey HA, 1993, Protein Sci 2:1959-1965). Here we report on the effect of replacement of aminolevulinate synthase lysine-313 by alanine, histidine, and glycine, using site-directed mutagenesis. Mutant enzymes were purified to homogeneity, and the purification yields were similar to those of the wild-type enzyme. Although their absorption spectra indicate that the mutant enzymes bind pyridoxal 5'-phosphate, they bind noncovalently. However, addition of glycine to the mutant enzymes led to the formation of external aldimines. The formation of an external aldimine between the pyridoxal 5'-phosphate cofactor and the glycine substrate is the first step in the mechanism of the aminolevulinate synthase-catalyzed reaction. In contrast, lysine-313 is an essential catalytic residue, because the K313-directed mutant enzymes have no measurable activity. In summary, site-directed mutagenesis of the aminolevulinate synthase active-site lysine-313, to alanine (K313A), histidine (K313H), or glycine (K313G) yields enzymes that bind the pyridoxal 5'-phosphate cofactor and the glycine substrate to produce external aldimines, but which are inactive. This suggests that lysine-313 has a functional role in catalysis.